EXPLORING THE ROLE OF BRAINSTORMING IN ENHANCING AUDIT QUALITY - Hofandrik Lase; Arya Pradipta; Magda Siahaan (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2024)
The objective of this study is to investigate the impact of brainstorming on audit quality, while taking into consideration factors such as audit tenure, accountability, and auditor competence. This paper is descriptive and uses a quantitative approach, using primary data, namely 211 auditors who work at the Public Accounting Firm in Jakarta, Indonesia. Purposive sampling is utilized in the sampling method, with information being gathered through a survey and then analyzed through the Partial Least Square approach. Audit tenure, accountability, auditor competency, and brainstorming positively affect audit quality. Meanwhile, brainstorming strengthens the influence of accountability on audit quality, although it cannot moderate audit tenure and auditor competency on audit quality. Brainstorming cannot be separated from the culture and environment of the client company or auditor's office, so the auditors' underlying behavior patterns should be upgraded to improve the audit quality. It is still rare for the authors to find that brainstorming moderates the influence of external auditors' professionalism on audit quality.